Roles and change strategies of low carbon communities - Mayne, R; Hamilton, J; Lucas, K (EVALOC, 2013)
It is widely recognised that the transition to a low carbon future will require action by distinct actors across different levels and sectors. Yet while there is much analysis about what needs to change there is less clarity in the UK about who is responsible for change or how to achieve the transition. The paper helps to address this limitation by assessing these questions in relation to the change strategies of a number of low carbon communities (LCCs) in the UK. Drawing on emerging findings from the EVALOC1 research project in the UK, and other relevant sources, it compares the design of three local ‘community group’ with two local ‘partnership’ domestic carbon reduction strategies. It assesses their contributions and limits and investigates the extent to which the different change strategies contribute to the multiple influences on energy use identified in the literature. The findings indicate that both local authorities and community groups are making important contributions to domestic carbon reduction. However, LCCs have an uneven spread, capacity and reach, and community groups need to be seen as complements, rather than substitutes to, local authority action. The research also raises questions about the effectiveness and sustainability of a government strategy that relies largely on voluntary and market approaches, shows how local action is constrained by wider structural barriers and points to the need for a stronger and more active role for national government.